PENGELOLAAN LAPOR HENDI DI KOTA SEMARANG TAHUN 2017 KAJIAN SUMBER DAYA KEBIJAKAN - Muzaki, Muhamad Shulkhan; Manar, Dzunuwanus Ghulam (Journal of Politic and Government Studies, 2018)
The Ombudsman study explains the lack of complaints not because of the performance of public services either, in fact people are reluctant to complain because it is considered not to bring any changes to the public service. The central government develops the LAPOR / Aspirations and Online People's Complaint Service, based on electronic applications, targeting in 2017 all Institutions / Ministries / BUMN / D / LGs can be integrated into the LAPOR program in order to improve the quality of public services. In 2016 the city government of Semarang began to implement the LAPOR policy with the name of Lapor Hendi. This policy is categorized as the use of electronic facilities by government / e-government in the field of public services, specifically the public service complaints management section.The objective of this research is to know Lapor Hendi process as public policy which is electronic from the side of its policy resources, using theory of policy resources from Harvard JFK School Of Government study, that is from Support, Capacity and Value aspect. Researched with descriptive kuaitatif method, by way of data retrieval through interviews, observation, and literature study.The result of the research shows that from the support side, there is support from the regulation of mayor that regulate Lapor Hendi, commitment in the form of routine report discussions, the allocation of physical infrastructure as the facilities and infrastructure of the activity, and also the socialization of Lapor Hendi indirectly to the community. In terms of capacity, the financial program of Lapor Hendi has been allocated to APBD, institutional, human resources managers and implementers along with technology infrastructure has been provided for this program. In terms of benefits, there are 3 parties who get from the benefits of Lapor Hendi policy, the community both Semarang City and outside the city of Semarang that utilize the facilities of Semarang City, Semarang City Government, and Profit Organization.Keywords: public service, Lapor Hendi, public policy resources, Support, Capacity, Value.